Implementation of Quickbooks for Financial Management for the Aisyiah Colomadu Bustanul Teachers Association (IGABA) - Didit Purnomo; Mujiati; Setyowati, Eni; Yuni Prihadi Utomo; Daryono Subagyo; Maulidyah Indira Hasmari; Firly Meidhita Berliandini; Keisha Jenny Maulida Nugraha; Salma Salsabila Darojati; Novariani Putri Rienadi; Isnaeni Hasna Hanisah; Dewi Puji Astuti; Shafa Nabila; Siti Nurhayati (Universitas Muhammadiyah Surakarta, 2025)
This community service was carried out at IGABA Aisyiah Colomadu Karanganyar. The problem faced by IGABA is the lack of insight and management of financial administration by the HR Teachers and managers of TK Bustanul Atfal Aisyiah. Therefore, this community service is highly expected by partners. The target audience needs support in terms of infrastructure and human resources in realizing useful financial administration and can provide an example for other schools. The purpose of this community service activity is 1. to assist the target audience in carrying out activities 2. Help partners improve financial administration 3. Accompany partners in improving their ability to manage finances, The method used in this activity is the Focus Group Discussion method, direct practice, training, and mentoring. The output of this community service is in the form of published articles in journals, HAKI Posters, HAKI Videos, community service reports, news in the media and documentation that will be uploaded on online media.